Human CD8+HLA-DR+ Regulatory T Cells, Similarly to Classical CD4+Foxp3+ Cells, Suppress Immune Responses via PD-1/PD-L1 Axis - Machicote, Andres; Belén, Santiago; Baz, Placida; Billordo, Luis A.; Fainboim, Leonardo (Frontiers in Immunology, 2018)
We have previously identified a human CD8+HLA-DR+ regulatory T cell subset with the ability to suppress proliferation of autologous PBMCs responder cells through cell contact and CTLA-4 co-inhibitory molecule. The present study characterizes the complete phenotype of CD8+HLA-DR+ Treg cells which showed great similarities with classical CD4+ cells expressing forkhead box P3 (FOXP3). The shared features included the expression of programmed cell death protein 1 (PD-1), T-cell immunoreceptor with Ig and ITIM domains (TIGIT), C-C chemokine receptor type 4 and 5 (CCR4 and CCR5), low expression of CD127, and a memory and effector-like phenotype. CD8+HLA-DR+ Treg-induced suppression on CD8+ responder T cells was abrogated by an anti-PD1 neutralizing antibody. Anti-PD-1 did not abrogate the suppressor effect induced on responder CD4+ T cells. In addition, CD8+HLA-DR+ Treg induced a preferential death on responder CD8+ T cells. This effect was not reversed by PD-1 neutralization. After activation, most CD8+HLA-DR+ Treg acquire programmed death-ligand 1 (PD-L1) expression. Interestingly, PD-L1 may induce apoptosis through CD80 expressed on activated CD8+ responder T cells. After PBMCs stimulation, CD8+HLA-DR+ Treg cells showed an increased frequency of IFN- and TNF positive cells and higher degranulation. These data strongly argue against CD8+HLA-DR+ Treg being exhausted cells. Overall, the data presented in this study indicate that CD8+HLA-DR+ Treg and CD4+FOXP3+ Treg share phenotypic and functional features, which may provide cues to similar involvements in the control of antitumor immune responses and autoimmunity.